2018
DOI: 10.1159/000487714
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Variability: An Independent Risk Factor for Graft Loss and Death following Kidney Transplantation

Abstract: Background: Several studies have been performed to evaluate surrogate markers of long-term allograft function in renal transplant recipients. These include serum creatinine, estimated glomerular filtration rate (eGFR), slope of eGFR, and more recently eGFR variability. The aim of this study was to measure eGFR slope while assessing the variability of this slope and if high variability occurring at any time post-transplant was predictive of poorer long-term outcomes in a large cohort of kidney transplant recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Interestingly, in our cohort, the individual course of eGFR varied strongly between the 90 study participants. This strong variability has been previously reported [24, 25] and is not surprising, as many factors such as medication, donor characteristics, and general health status differ strongly not only between patients but also for the individual patient, and for medication. However, high variability of kidney function after KTx has been described as an independent risk factor for graft loss and death [24-26].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, in our cohort, the individual course of eGFR varied strongly between the 90 study participants. This strong variability has been previously reported [24, 25] and is not surprising, as many factors such as medication, donor characteristics, and general health status differ strongly not only between patients but also for the individual patient, and for medication. However, high variability of kidney function after KTx has been described as an independent risk factor for graft loss and death [24-26].…”
Section: Discussionsupporting
confidence: 69%
“…This strong variability has been previously reported [24, 25] and is not surprising, as many factors such as medication, donor characteristics, and general health status differ strongly not only between patients but also for the individual patient, and for medication. However, high variability of kidney function after KTx has been described as an independent risk factor for graft loss and death [24-26]. Thus, we used a mixed linear model including all available eGFR and bicarbonate values over the first year after KTx.…”
Section: Discussionsupporting
confidence: 69%
“…Few studies have assessed the association between graft function variability and outcomes among KTRs. 5 , 8 These studies were not able to incorporate graft function slope appropriately and failed to differentiate the association of graft function variability with death from those with graft failure, which are competing risk events posttransplantation. These studies also did not assess whether variability provides additional prognostic information for transplantation outcomes.…”
mentioning
confidence: 99%
“…Furthermore, changes in graft function over time as estimated by eGFR slope have been shown to be highly correlated with measured iothalamate GFR slopes in allograft recipients, thus providing valuable information for the trajectory of functional decline . In addition, it has been shown that eGFR slope is a strong predictor of long‐term kidney allograft outcome and may facilitate its prediction . While the overwhelming number of studies analysing pretransplant RRT modality did not incorporate data on actual allograft function, there are only two reports taking into account creatinine or eGFR, both failing to demonstrate graft function differences in recipients with pretransplant HD versus PD regimens.…”
Section: Discussionmentioning
confidence: 99%